Shear-, Sound-, and Light-Sensitive Nanoparticles for Thrombolytic Drug Delivery - Qu, Shu; Ding, Xingwei (Seminars in Thrombosis and Hemostasis, 2020)
Thrombotic diseases, as potentially induced by blood clots or vascular embolization, frequently occur with high rates of mortalities worldwide. Current drug thrombolysis, a primary clinical therapy, may increase fatal risk of hemorrhage when thrombolysis agents become systemically distributed. Given current thrombolysis limitations, some novel drug delivery systems based on nanoparticles have been recently exploited to achieve a more controlled release of loaded thrombolytic agents, able to respond to environmental changes, and resulting in a safer thrombolysis. In this review, the authors outline and discuss some prominent examples of early and recent thrombolytic agent delivery systems using controlled release by physical stimuli (shear, sound and light). Shear-sensitive systems are designed to exploit the specific biomechanical feature of thrombosis, that is, the increased blood shear stress. Sound- and light-sensitive systems reflect “remote control” of drug release by responding to external ultrasound or light stimulus. These smart thrombolytic drug delivery systems hold promise for more effective and safer future thrombolytic therapy.
Keywords: stimuli-responsive; thrombolysis; drug delivery; nanomedicine; particles